PENGARUH PUSAT KENDALI INTERNAL DAN EKSTERNAL, EFIKASI DIRI DAN KEPUASAN KERJA TERHADAP KOMITMEN KEORGANISASIAN KARYAWAN PADA PT. PASIFIK TEKNOLOGI INDONESIA - Desy Fitriani; Edi Purwanto (Universitas Bunda Mulia, 2019)
The purpose of this study was to examine the influence of internal locus of control, external locus of control, self-efficacy, and job satisfaction on organizational commitments. This research was conducted on employees of PT. Pacifik Teknologi Indonesia. The research used simple random sampling. Data collection was done by distributing questionnaires to 114 respondents. The result of the research shows that internal locus ofcontrol has a positive and significant effect on organizational commitment, external locus of control has a positive and significant effect on organizational commitment, then job satisfaction has a positive and significant effect on organizational commitment, but self-efficacy has not a positive and significant effect on organizational commitment. Simultaneously, internal locus of control, external locus of control, self-efficacy, and job satisfaction have a positive and significant effect on organizational commitment.Keywords: internal locus of control, external locus of control, self efficacy, job satisfaction, organizationalcommitment.